Workplace Violence Against Doctors and Nurses in Public Healthcare Services in AL- Majmaah City, Saudi Arabia - Alfhaid, Fahad Mohammad; Loni, Shamshad Begum; Aljulifi, Mohammed Zaid; Alturki, Raghad Abdulaziz Ahmad; AlGhannam, Raghad Ghannam Ibrahim; Almutairi, Batool Awn Allah Khalifah; Almutairi, Maram Awn Allah Khalifah (Majalah Kedokteran Bandung, 2025)
Workplace violence raises a significant concern in healthcare settings, with healthcare workers being at risk of physical and emotional harms. This phenomenon is, however, rarely investigated in Al-Majmaah city, Saudi Arabia. This study sought to estimate the prevalence of workplace violence against doctors and nurses working in public healthcare facilities in Al-Majmaah city. A cross-sectional study was conducted in public health facilities in Al-Majmaah city, Saudi Arabia, from June to August 2022. Healthcare workers were recruited to participate in a self-administered online questionnaire, which collected data on sociodemographic information, workplace violence exposure, and attitudes towards violence. Of the total participants, 41.9% reported experiencing workplace violence. The majority of incidents occurred in health institutions, with 92.3% involving verbal abuse, 2.6% physical violence, or both. Patients' families were responsible for 48.7% of the violence, followed by the patients themselves (43.6%). In response to violence, healthcare workers reported various coping mechanisms, including pretending the incident never happened (23.1%), attempting to stop the perpetrator (23.1%), and protecting themselves (18%). Regarding system satisfaction, 14% remained indifferent, 16% were dissatisfied, and 2% were satisfied. Furthermore, 15.1% of participants experienced disturbed thoughts or images of the attack, 14% avoided thinking or talking about incidents, and 11.8% were unaffected. Workplace violence is a significant problem affecting healthcare workers in public healthcare facilities in Al-Majmaah city, Saudi Arabia. The high prevalence of verbal abuse and physical violence highlights the need for effective prevention and intervention strategies to ensure a safe working environment for healthcare workers.